Synthesis and crystal structure of bis(2-phthalimidoethyl)ammonium chloride dihydrate - Barry S. Young; Jamie L. Lee; Milan Gembicky; Jake Bailey; Gary L. N. Smith (Acta Crystallographica Section E: Crystallographic Communications, 2023)
The title compound {systematic name: bis[2-(1,3-dioxoisoindol-2-yl)ethyl]azanium chloride dihydrate}, C20H18N3O4+·Cl−·2H2O, is a phthalimide-protected polyamine that was synthesized by a previous method. It was characterized by ESI–MS, 1H NMR, and FT–IR. Crystals were grown from a solution of H2O and 0.1 M HCl. The central nitrogen atom is protonated and forms hydrogen bonds with the chloride ion and a water molecule. The two phthalimide units make a dihedral angle of 22.07 (3)°. The crystal packing features a hydrogen-bond network, two-coordinated chloride, and off-set π–π stacking.